THE ETHICAL PROBLEMS OF ARCHITECTURAL RECONSTRUCTION – HUNGARIAN CASE STUDIES - Ádám Arnóth (Ochrona Dziedzictwa Kulturowego)
Modernist practice, the modernist way of conservation and restoration, is against historicism, against reconstruction. The main rule is: deceit, forgery, falsification is forbidden. Despite this, some reconstructions were undertaken in Hungary, and recently the pressure for reconstructions has become even greater. Unfortunately, the categories of listed buildings, open-air museums and Disneyland are sometimes mixed up by the public and even by decision makers.